2015
DOI: 10.5455/medarh.2015.69.232-235
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Inflammation and Lipoprotein (a) with Hypercoagulability in Hemodialysis Patients

Abstract: Background:Inflammatory and procoagulant markers are potential mediators for the cardiovascular risk in hemodialysis patients. Lipoprotein (a) [Lp(a)], is another important risk factor with inflammatory and procoagulant effects.Materials and methods:In 78 hemodialysis patients and 40 controls, C-reactive protein (CRP), Interleukin-6 (IL-6), lipoprotein (a) [Lp (a)], fibrinogen, D-dimer, von Wilebrand factor (vWF) and serum albumin were determined.Results:CRP, IL-6, Lp(a), fibrinogen, D-dimer and vWF, were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…[33][34][35] Moreover, hemodialysis is another risk factor for procoagulant and inflammatory effects in ESRD patients. 36 Our study showed the prevalence of CKD is higher in CRVO subgroup than BRVO subgroup. Similarly, ESRD patients had higher prevalence of CRVO than BRVO.…”
Section: Discussionmentioning
confidence: 50%
“…[33][34][35] Moreover, hemodialysis is another risk factor for procoagulant and inflammatory effects in ESRD patients. 36 Our study showed the prevalence of CKD is higher in CRVO subgroup than BRVO subgroup. Similarly, ESRD patients had higher prevalence of CRVO than BRVO.…”
Section: Discussionmentioning
confidence: 50%
“…According to the Speedwell Study, a positive correlation was shown between hs-CRP and D-dimer and a much stronger association between hs-CRP and fibrinogen in heart disease 30 , and these findings correlate with our findings as baseline. Also, according to a recent research, hs-CRP correlated positively with fibrinogen and D-dimer in hemodialysis patients 31 . These findings correlate with our findings which showed a strong positive correlation between hs-CRP and either D-dimer or fibrinogen in the males as baseline.…”
Section: Discussionmentioning
confidence: 82%
“…This recent study with 52 dyslipidemic subjects showed a strong and significant positive correlation between the serum hsCRP Levels with the serum triglycerides [15]. Some other stud-ies showed that CRP and IL-6 levels correlated with significance positively with Lp(a) levels in hemodialysis patients [16]. Lp(a) levels showed no significant correlations with glycemic control parameters nor insulin and triglyceride levels in study with diabetic patients [17].…”
Section: Discussionmentioning
confidence: 90%